Implementation of Brand Image through Service Quality in PERISAI Agency Marketing Program - Fadhilah, Laila Luthfiana; Marsasi, Endy Gunanto (Jurnal Manajemen Bisnis dan Keuangan, 2024)
This research is a study that examines insurance service companies that have several products. This study aims to determine the application of brand image through service quality in PERISAI agency marketing. This study uses descriptive qualitative research methods and data collected through observation, interviews, company secondary data, and documentation. The analysis technique used is SWOT analysis. The results of this study indicate that the marketing strategy of the PERISAI program provides good benefits for the community (agents and participants). PERISAI was formed with the hope that workers can have access to services for the protection programs contained in BPJS Ketenagakerjaan. The programs contained in BPJS Ketenagakerjaan include death benefits (JKM), work accident insurance (JKK), old age security (JHT), and pension benefits (JP). This evaluation is carried out in order to increase the number of BPJS Ketenagakerjaan membership, especially in the field of non-wage recipient workers. This evaluation uses the theory of service quality with the concept of brand image which will be applied to the PERISAI marketing program at BPJS Ketenagakerjaan.